From early microstructural evolution to intergranular crack propagation in SAC solders under thermomechanical fatigue. (November 2021) - Ben Romdhane, E.; Roumanille, P.; Guédon-Gracia, A.; Pin, S.; Nguyen, P.; Frémont, H.
Abstract: Due to the complexity of the initial microstructure of lead-free solder joints combined to a failure mechanism that is not yet fully understood, lifetime predictions of SnAgCu solder joints remain a challenging task. In this work, Sn3.0Ag0.5Cu (SAC305) solder joints microstructural evolution during thermal cycling is presented. Electron Back Scattered Diffraction (EBSD) analyses were conducted to assess the SAC305 microstructure changes corresponding to different number of thermal cycles. The goal is to define the role of each microstructural phenomenon in the solder joint fatigue life by correlation with electrical failure monitoring results along the cycling test. Experimental observations show that crack initiation starts very early and precedes the propagation of β-Sn grains recrystallization in the solder high strain area. However, solder joint lifetime is controlled by recrystallization and Ag3 Sn particles coarsening which are the most important phenomena leading to the intergranular crack propagation. Highlights: Crack initiation starts precedes the propagation of β-Sn grains recrystallization in the solder high strain area. Solder joint lifetime is controlled by tin grains recrystallization and Ag3 Sn particles coarsening. Intergranular crack propagation requires a well-defined degree of recrystallization coupled with an Ag3 Sn particle density threshold.